A New Species of Crab-Spider Under the Genus Thomisus Walckenaer, 1805 (Araneae: Thomisinae: Thomisidae) From Bangladesh: A new species of crab-spider under the genus Thomisus (Journal of the Asiatic Society of Bangladesh, Science, 2023)
Taxonomic description of a new species of crab-spider genus Thomisus Walckenaer, 1805 is provided herewith. The species Thomisus aruni n. sp. was identified as new to science. The paper contains an illustrated description of the species together with the generic diagnosis and distribution of the species.J. Asiat. Soc. Bangladesh, Sci. 49(2): 193-201, December 2023